Relationship Between Stunting Incidents and Speech Delay in Toddlers at Posyandu X Cimahi - Dewi Umu Kulsum; Sania Shalsabila; Dwi Hastuti (UIMA Press, 2023)
Background: Stunting is a condition in toddlers with shorter growth compared to children their age. Inadequate nutritional intake in stunted children can inhibit brain growth, affecting child growth and development. Objectives: This study aims to determine the relationship between the incidence of stunting and speech delay in toddlers at Posyandu X Cimahi Methods: This study was designed using observational analytics with a cross-sectional study design approach. Sampling was carried out using a stratified random sampling technique of 47 respondents. The instrument used for stunting screening is a microtome/infantometer, and a Denver II is used for speech delay. Data analysis was performed univariately and bivariate with the Spearman correlation test. Results: This study's results illustrate a relationship between the incidence of stunting and speech delay in toddlers at Posyandu X Cimahi. Conclusion: Statistical results show a value of 0.021 (p <0.05) with a correlation coefficient of 0.336 which means moderate correlation strength.